2014
DOI: 10.5194/nhess-14-3331-2014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a rare winter hailstorm event over Delhi, India on 17 January 2013

Abstract: Abstract. This study analyzes the cause of the rare occurrence of a winter hailstorm over New

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Of those available in the literature, studies such as Sing and Mandal (2014) found that the Goddard scheme has a "slightly better" performance than other schemes. This conclusion is also supported by studies such as Choudhury and Das (2017) and has been used in hailstorm studies such as Chevuturi et al (2014). The impact of the downscaling ratio on the rainfall simulations is addressed next.…”
Section: Model Configuration and Experimental Setupmentioning
confidence: 56%
“…Of those available in the literature, studies such as Sing and Mandal (2014) found that the Goddard scheme has a "slightly better" performance than other schemes. This conclusion is also supported by studies such as Choudhury and Das (2017) and has been used in hailstorm studies such as Chevuturi et al (2014). The impact of the downscaling ratio on the rainfall simulations is addressed next.…”
Section: Model Configuration and Experimental Setupmentioning
confidence: 56%
“…Large scale and synoptic characteristics of the winter hailstorm and non-winter hailstorm has been discussed in previous papers (Chevuturi et al 2014;Chevuturi and Dimri 2015). In high resolution model simulations (for resolutions smaller than 3 km) cloud microphysics scheme estimates the precipitation rather than cumulus parameterization schemes (Chevuturi et al 2014).…”
Section: Aprilmentioning
confidence: 91%
“…As this study is based on numerical simulation method, model simulated output needs to be verified. The verification analysis and physical processes associated of the winter and non-winter hailstorm has been described in previous papers (Chevuturi et al 2014;Chevuturi and Dimri 2015). The synoptic information of the recent events also can be compiled.…”
Section: Synoptic Situationmentioning
confidence: 99%
See 2 more Smart Citations